A lithium supplement material, a lithium supplement diaphragm and a preparation method thereof
By applying a lithium supplement material for the application of nuclear shell structure on the lithium ion battery diaphragm, the lithium supplement layer is formed, and the problem of the effect of the existing diaphragm coating material affects the battery performance, and the battery performance is improved and the safety is improved.
Patent Information
- Application Number
- CN202410332419.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-03-21
AI Technical Summary
The coating materials of existing lithium-ion battery separators are mostly chemically inert materials, which affects the electrochemical performance of the positive and negative electrodes of the battery and is difficult to effectively improve the battery performance.
The lithium supplement material with a nuclear shell structure is used as the kernel, and the three -yuan or quad -via active material is used as the cover layer to form a lithium supplement layer to avoid introducing non -active conductive carbon substances, enhanced conductive and conductive and electrical and electrical resistance and electrical and electrical properties. Lithium ion conduction.
Through the slow -release effect of the lithium layer, effectively improve the performance of the battery, ensure the normal play of the basic function of the diaphragm, avoid short -circuit risks, and improve the battery discharge capacity, cycle life and safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a lithium supplement material, a lithium supplement diaphragm and a preparation method thereof. Background Art
[0002] With the development of science and technology, lithium-ion batteries have been widely used in many fields due to their advantages such as high energy density, high rated voltage, no memory effect and long cycle life. Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, electrolyte and diaphragm. Among them, the diaphragm, as a key inner component, plays a vital role.
[0003] The main function of lithium-ion battery separator is to separate the positive and negative electrodes, prevent the positive and negative electrodes from contacting and causing a short circuit in the battery, and allow the free passage of lithium ions to conduct lithium ions. It must ensure both the safety of the battery and the efficient operation of the battery. Therefore, the performance of the separator directly affects the discharge capacity, cycle life and safety of the lithium-ion battery.
[0004] According to the different preparation materials and processes, lithium-ion battery separators are mainly divided into substrate separators and coating separators. Among them, the substrate separators mainly include polyolefin separators, inorganic ceramic separators, composite separators, etc. The coating separator is coated with a thin layer of coating on the surface of the substrate separator to enhance the characteristics of the separator, such as improving the pore size, distribution, mechanical strength, chemical stability, etc. of the separator. Currently, common coating materials include inorganic coatings such as alumina coatings and silicon nitride coatings, organic coatings such as polymer coatings, and inorganic-organic composite coatings. These coatings can not only improve the high temperature resistance, mechanical strength, chemical stability, etc. of the separator, but also improve the migration efficiency of lithium ions, thereby improving the electrochemical performance of the battery.
[0005] However, most of the existing coatings are chemically inert materials, which to some extent affect the electrochemical performance of the positive and negative electrodes of the battery. Therefore, it is still necessary to develop a new coating membrane solution to ensure the basic function of the membrane and effectively improve or enhance the performance of the battery. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a lithium-supplementing material, a lithium-supplementing diaphragm and a preparation method thereof. The lithium-supplementing material has a lithium-supplementing agent core and a ternary or quaternary active material shell. The lithium-supplementing diaphragm is obtained by forming a lithium-supplementing layer on a diaphragm substrate with the lithium-supplementing material. The use of the lithium-supplementing diaphragm can not only ensure the basic functions of the diaphragm, but also slowly release lithium supplement, thereby effectively improving and enhancing the performance of the battery.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a lithium supplement material, which has a core-shell structure. The core includes a lithium supplement agent, and the shell includes LiNi 1-x-y Co x M y O2, where 0 < x ≤ 0.5, 0 < y ≤ 0.5, x + y < 1, and M includes Mn and / or Al.
[0009] The lithium supplement material of the present invention uses a lithium supplement agent as the inner core and a ternary or quaternary active material (such as NCM, NCA, etc.) as the coating layer, so that the coating layer can conduct electricity and ions. This not only enhances the conductivity of the lithium supplement material but also provides active Li ions, thus having a sufficient lithium supplement amount. Therefore, excellent and stable lithium supplement effects can be achieved. In the prior art, the lithium supplement materials applied to the separator often increase non-active conductive carbon in the coating slurry. However, when the obtained lithium supplement material of the present invention is applied to the separator to form a coated separator, it can avoid introducing non-active conductive carbon substances and increasing the risk of short circuit, and can ensure the normal functioning of the basic functions of the separator. Moreover, the functions of lithium supplement and lithium ion conduction can effectively improve the performance of the battery.
[0010] The following are the preferred technical solutions of the present invention, but not the limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved.
[0011] As a preferred technical solution of the present invention, the lithium supplement agent is at least one of Li2O, Li2S, LFO, LNO, and the complexes Li2S / Co and Li2O / Co.
[0012] Preferably, the particle size of the lithium supplement material is 20 nm to 20 μm, such as 20 nm, 60 nm, 100 nm, 300 nm, 600 nm, 800 nm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 18 μm, or 20 μm, etc. Preferably, it is 100 nm to 1 μm, but not limited to the listed values. Other unlisted values within the above numerical range are equally applicable.
[0013] Preferably, the thickness of the shell is 2 to 2000 nm, such as 2 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or 2000 nm, etc. Further preferably, it is 2 to 1000 nm, but not limited to the listed values. Other unlisted values within the above numerical range are equally applicable.
[0014] Second aspect, the present invention provides a preparation method of the lithium supplement material described in the first aspect, the preparation method comprising:
[0015] Mixing a lithium supplement precursor with a shell raw material to form a core-shell coating, and mixing and sintering the core-shell coating with a lithium source to obtain the lithium supplement material.
[0016] The preparation method of the lithium supplement material of the present invention is simple, low in cost, compatible with existing preparation equipment and production lines, suitable for mass production, and can be widely applied to process production.
[0017] As a preferred technical solution of the present invention, the preparation method comprises: first mixing and stirring the lithium supplement precursor with a solvent, then adding the shell raw material and mixing and stirring, then adding a mixed solution of ammonia water and a strong base and mixing and stirring, and titrating and precipitating a shell precursor through the mixed solution to form a coating of the shell precursor on the lithium supplement precursor at the same time. After obtaining the core-shell coating, washing and drying the core-shell coating and then mixing and sintering with a lithium source.
[0018] Preferably, the shell raw material includes soluble nickel salt, soluble cobalt salt and soluble M salt.
[0019] Preferably, the mass ratio of the soluble nickel salt to the lithium supplement precursor is (1-9):(10-90), such as 1:10, 3:10, 5:10, 7:10, 9:10, 1:25, 3:25, 5:25, 7:25, 9:25, 1:50, 3:50, 5:50, 7:50, 9:50, 1:75, 3:75, 5:75, 7:75, 9:75, 1:90, 3:90, 5:90, 7:90 or 8:90, etc., but not limited to the listed values, and other unlisted values within the above value range are equally applicable.
[0020] Preferably, the core-shell coating also has a core-shell structure, wherein the core of the core-shell coating is the lithium supplement precursor and the shell is the shell precursor; the shell precursor is Ni 1-x-y Co x M y (OH)2, 0 < x ≤ 0.5, 0 < y ≤ 0.5, x + y < 1, and M includes Mn and / or Al.
[0021] Preferably, the drying temperature is 50-120 °C, such as 50 °C, 55 °C, 60 °C, 65 °C, 70 °C, 75 °C, 80 °C, 90 °C, 100 °C, 110 °C or 120 °C, etc., and the time is 1-3 h, such as 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc., but not limited to the listed values, and other unlisted values within the above value range are equally applicable.
[0022] Preferably, the sintering temperature is 600-1200°C, for example 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, and the time is 3-7h, for example 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 6h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0023] Preferably, in the mixing and stirring of the lithium supplement agent precursor and the solvent, the solvent includes but is not limited to water.
[0024] Preferably, the amount of the lithium source and the core-shell coating is controlled according to the molar ratio of lithium to nickel (10-100): (3-9), for example, 10:3, 20:3, 20:5, 20:5.3, 20:5.5, 20:5.8, 20:6, 20:6.2, 20:6.5, 20:6.8, 20:7, 20:7.3, 20:7.5, 20:7.8, 20:8, 20:8.3, 20:8.5, 20:8.8 or 20:9, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0025] In a third aspect, the present invention provides a lithium-supplementing diaphragm, comprising a diaphragm and a lithium-supplementing layer disposed on the diaphragm, wherein the lithium-supplementing layer contains the lithium-supplementing material described in the first aspect or contains the lithium-supplementing material obtained by the preparation method described in the second aspect.
[0026] The lithium-supplementing diaphragm of the present invention can replenish the loss of active lithium in the process of generating SEI film during the first cycle, so the lithium-supplementing layer is preferably arranged on the side of the diaphragm substrate facing the positive electrode. The core and shell of the lithium-supplementing material in the lithium-supplementing layer can both provide active lithium, and the coating layer formed by the ternary or quaternary active material also improves the electronic conductivity of the internal lithium compound. Therefore, the use of the lithium-supplementing diaphragm can effectively improve the performance of the battery. The lithium-supplementing material and lithium-supplementing diaphragm provided by the present invention have good compatibility with the current commercial positive and negative electrodes, and there is no need to adjust and redesign the electrolyte and battery manufacturing process, and are very suitable for current secondary lithium-ion batteries.
[0027] As a preferred technical solution of the present invention, the lithium replenishing layer is arranged on the side of the separator facing the positive electrode.
[0028] Preferably, the lithium replenishing layer further contains a binder.
[0029] Preferably, the binder accounts for 0.5% to 20% of the mass of the lithium replenishing layer, for example 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0030] Preferably, the binder comprises a conductive polymer.
[0031] Preferably, the conductive polymer includes at least one of polyacetylene, polypyrrole, polyaniline, polythiophene or polyfuran.
[0032] In the preparation of the lithium replenishing diaphragm of the present invention, a conductive polymer is preferably used as a binder to construct a lithium replenishing layer together with the lithium replenishing material. In addition to increasing the adhesion so that the lithium replenishing material is combined with the diaphragm substrate, the conductive polymer itself can construct a conductive network structure to make the lithium replenishing material and the positive electrode material conductive and form an electric potential difference with the negative electrode, thereby improving the performance of the battery and avoiding the influence of using conventional non-conductive binders (such as polyvinylidene fluoride PVDF).
[0033] In a fourth aspect, the present invention provides a method for preparing the lithium supplementing diaphragm according to the third aspect, the method comprising:
[0034] A lithium supplement layer slurry is prepared, and the obtained lithium supplement layer slurry is coated on the diaphragm to form a lithium supplement layer, thereby obtaining a lithium supplement diaphragm.
[0035] It should be noted that the present invention does not limit the specific selection of the diaphragm. The diaphragms that can be used in batteries in the prior art are all suitable for constructing the lithium supplement diaphragm of the present invention, and should be reasonably selected and adjusted according to actual needs. Exemplarily, the diaphragm includes a PE diaphragm (polyethylene diaphragm).
[0036] As a preferred technical solution of the present invention, the solvent for preparing the lithium replenishing layer slurry includes at least one of N-methylpyrrolidone, acetone, dimethyl carbonate (DMC) and anhydrous ethanol. For example, typical but non-limiting combinations include a combination of N-methylpyrrolidone and acetone, a combination of N-methylpyrrolidone and dimethyl carbonate, a combination of N-methylpyrrolidone and anhydrous ethanol, a combination of acetone and dimethyl carbonate, a combination of acetone and anhydrous ethanol, and the like.
[0037] Preferably, taking the mass of the lithium replenishing layer slurry as 100%, the mass of the lithium replenishing material accounts for 20% to 70%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc., the mass of the binder accounts for 0.5% to 20%, for example, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 7%, 8%, 10%, 13%, 15%, 18% or 20%, etc., and the mass of the solvent accounts for 10% to 70%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0038] In a fifth aspect, the present invention provides a lithium-ion energy storage device comprising the lithium-supplementing material described in the first aspect or the lithium-supplementing diaphragm described in the third aspect.
[0039] Preferably, the lithium ion energy storage device comprises a lithium ion battery.
[0040] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0041] The lithium supplement material of the present invention uses a lithium supplement agent as a core and a ternary or quaternary active material as a coating layer, so that the coating layer can conduct electricity and ions, which not only enhances the conductivity of the lithium supplement material, but also provides active Li ions and has a sufficient amount of lithium supplement, thereby achieving an excellent and stable lithium supplement effect.
[0042] When the obtained lithium replenishing material is applied to the diaphragm to form a coated diaphragm, the loss of active lithium in the process of forming the SEI film can be replenished during the first cycle, which can ensure the normal performance of the basic functions of the diaphragm and avoid the introduction of inactive conductive carbon materials to increase the risk of short circuit. The lithium replenishment and lithium ion conduction functions provided can effectively improve the performance of the battery.
[0043] The present invention uses a conductive polymer as a binder to construct a lithium replenishing layer together with the lithium replenishing material. In addition to increasing the adhesion so that the lithium replenishing material is combined with the diaphragm substrate, the conductive polymer itself can construct a conductive network structure to make the lithium replenishing material and the positive electrode material conductive and form an electric potential difference with the negative electrode, thereby improving the performance of the battery and avoiding the impact of using conventional non-conductive binders (such as polyvinylidene fluoride PVDF). DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0045] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0046] Example 1
[0047] This embodiment provides a lithium supplement material, and the preparation method of the lithium supplement material includes:
[0048] 1) Li2CO3 is used as a lithium supplement precursor and is put into a stirring tank filled with water; then a shell raw material is also put into the stirring tank to stir and mix the lithium supplement precursor, the shell raw material and the solvent water, wherein the shell raw material is nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 8:1:1, and the mass ratio of the lithium supplement precursor to nickel sulfate is controlled to be 5:1;
[0049] 2) Use a mixed solution of ammonia and strong base NaOH (molar ratio of 1:1) to titrate into the stirring tank to generate Ni on the surface of Li2CO3 0.8 Co 0.1 Mn 0.1 (OH)2 particle coating (shell precursor) to form a core-shell coating;
[0050] 3) washing and drying the material in the stirring tank obtained in step 2), wherein the drying temperature is 80°C and the drying time is 2 hours; after drying, mixing with the lithium source LiOH, controlling the molar ratio of Ni element in the core-shell coating to Li in the lithium source to be 8:10, and then sintering at 800°C for 5 hours to obtain a lithium supplement material, wherein the core of the lithium supplement material is Li2O, and the chemical formula of the lithium supplement material is: LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0051] In the lithium supplement material obtained in this embodiment, the particle size of the lithium supplement agent is 500 nm; and the thickness of the shell of the lithium supplement material is 50 nm.
[0052] Example 2
[0053] This embodiment provides a lithium supplement material, and the preparation method of the lithium supplement material is as follows:
[0054] 1) Fe2O3 is used as a lithium supplement agent precursor and is put into a stirring tank filled with water; then a shell raw material is also put into the stirring tank to stir and mix the lithium supplement agent precursor, the shell raw material and the solvent water, wherein the shell raw material is nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 8:1:1, and the mass ratio of the lithium supplement agent precursor to nickel sulfate is controlled to be 5:1;
[0055] 2) Use a mixed solution of NaOH and strong base (molar ratio of 1:1) to titrate into the stirring tank to generate Ni on the surface of Fe2O3 0.8 Co0.1 Mn 0.1 (OH)2 particle coating (shell precursor) to form a core-shell coating;
[0056] 3) washing and drying the material in the stirring tank obtained in step 2), wherein the drying temperature is 80°C and the drying time is 2 hours; after drying, mixing with the lithium source LiOH, controlling the molar ratio of Ni in the core-shell coating to Li in the lithium source to be 8:20, and then sintering at 800°C for 5 hours to obtain a lithium supplement material, wherein the core of the lithium supplement material is LFO, and the chemical formula of the lithium supplement material is: LiNi 0.8 Co 0.1 M 0.1 O2.
[0057] In the lithium supplement material obtained in this embodiment, the particle size of the lithium supplement agent is 800 nm; and the thickness of the shell of the lithium supplement material is 60 nm.
[0058] Example 3
[0059] This embodiment provides a lithium supplement material. The preparation method of the lithium supplement material is to adjust the lithium supplement agent precursor from Li2CO3 to single substance S.
[0060] 1) Using single substance S as a lithium supplement agent precursor, put it into a stirring tank filled with water; then put the shell raw material into the stirring tank, so that the lithium supplement agent precursor, the shell raw material and the solvent water are stirred and mixed, wherein the shell raw material is nickel sulfate, cobalt sulfate and manganese sulfate with a molar ratio of 5:2:3, and the mass ratio of the lithium supplement agent precursor and nickel sulfate is controlled to be 10:1;
[0061] 2) Use a mixed solution of ammonia water and strong base NaOH (molar ratio of 1:1) to titrate into the stirring tank to generate Ni on the surface of the elemental S. 0.5 Co 0.2 Mn 0.3 (OH)2 particle coating (shell precursor) to form a core-shell coating;
[0062] 3) washing and drying the material in the stirring tank obtained in step 2), wherein the drying temperature is 80°C and the drying time is 2 hours; after drying, mixing with the lithium source Li2O, controlling the molar ratio of Ni in the core-shell coating to Li in the lithium source to be 8:20, and then sintering at 800°C for 5 hours to obtain a lithium supplement material, wherein the core of the lithium supplement material is L2S, and the chemical formula of the lithium supplement material is: LiNi 0.5 Co 0.2 Mn 0.3 O2.
[0063] In the lithium supplement material obtained in this example, the particle size of the lithium supplement agent is 600 nm; and the thickness of the shell of the lithium supplement material is 70 nm.
[0064] Comparative Example 1
[0065] This comparative example only uses the lithium supplement agent in Example 1 as the lithium supplement material.
[0066] Comparative Example 2
[0067] This comparative example only uses the shell material in Example 1, namely the ternary active material LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as a lithium supplement material.
[0068] Comparative Example 3
[0069] This comparative example provides a lithium supplement material having a core-shell structure. The only difference from Example 1 is that the shell of this comparative example is a carbon coating layer with the same thickness as the shell layer of Example 1.
[0070] Comparative Example 4
[0071] This comparative example provides a lithium supplement material, and the preparation method of the lithium supplement material comprises:
[0072] Li2CO3 is used as a lithium supplement precursor, and Ni 0.8 Co 0.1 Mn 0.1 (OH)2 powder mixing, and control Li2CO3 and Ni 0.8 Co 0.1 Mn 0.1 The mass ratio of (OH)2 powder is 6.7:1; after mixing the lithium supplement agent precursor and shell precursor dry powder, calcination is carried out at a temperature of 800°C and a calcination time of 5h to form the final lithium supplement material of Li2O and LiNi 0.8 Co 0.1 Mn 0.1 A particle mixture of O2.
[0073] The mass conversion of the powder in Comparative Example 4 is consistent with that in Example 1. In Example 1, the ternary material precursor is in situ grown on the surface of Li2CO3 through the synthesis process of the ternary material precursor. After calcination and synthesis, the core is Li2O and the shell is the coated LiNi 0.8 Co 0.1 Mn 0.1 O2 material, comparative example 4 is consistent with the traditional ternary material composite lithium supplement method, Li2CO3 and Ni 0.8 Co 0.1 Mn 0.1 (OH)2 mixed sintering cannot generate an in-situ coated core-shell structure, only Li2O and LiNi 0.8 Co 0.1 Mn 0.1The particle mixture of O2 cannot effectively improve the conductivity of Li2O.
[0074] Application Example 1
[0075] This application example provides a lithium-supplementing diaphragm, and a method for preparing the lithium-supplementing diaphragm includes:
[0076] The lithium replenishing material of Example 1, binder PEDOT (poly 3,4-ethylenedioxythiophene) and solvent NMP were prepared into a lithium replenishing layer slurry according to a mass ratio of 50:1:49. The lithium replenishing layer slurry was coated on one surface of the PE diaphragm substrate with a coating thickness of 3 μm. The coating was dried in an oven at 85° C. for 10 min to obtain a lithium replenishing diaphragm.
[0077] Application Example 2
[0078] This application example provides a lithium-supplementing diaphragm. The method for preparing the lithium-supplementing diaphragm is to replace the lithium-supplementing material of Example 1 with the lithium-supplementing material of Example 2, and reduce the amount of binder, so that the mass ratio of the lithium-supplementing material, the binder and the solvent is adjusted from 50:1:49 to 50:0.497:49. Apart from this, other conditions are exactly the same as those of Application Example 1.
[0079] Application Example 3
[0080] This application example provides a lithium-supplementing diaphragm. The method for preparing the lithium-supplementing diaphragm is to replace the lithium-supplementing material of Example 1 with the lithium-supplementing material of Example 3, and increase the amount of binder so that the mass ratio of the lithium-supplementing material, the binder and the solvent is adjusted from 50:1:49 to 50:24.75:49. Apart from this, the other conditions are exactly the same as those of Application Example 1.
[0081] Application Example 4
[0082] This application example provides a lithium-replenishing diaphragm. The method for preparing the lithium-replenishing diaphragm is to replace the binder PEDOT with polyvinylidene fluoride PVDF, and keep the amount of the binder unchanged. Apart from this, other conditions are exactly the same as those in Application Example 1.
[0083] Application Comparative Examples 1-4
[0084] Application Comparative Examples 1-4 respectively provide a diaphragm, and the method for preparing the diaphragm is to replace the lithium-supplementing material of Example 1 with the lithium-supplementing materials of Comparative Examples 1-4 respectively. Apart from this, other conditions are exactly the same as those of Application Example 1.
[0085] Application Comparative Example 5
[0086] This comparative example uses the PE diaphragm substrate in Example 1 as the diaphragm.
[0087] The diaphragms obtained according to the corresponding use cases and application comparisons were tested:
[0088] (1) The internal resistance of the diaphragm was tested according to the method of GB / T36363-2018, and the results are recorded in Table 1;
[0089] (2) The diaphragms obtained from the above-mentioned application examples and comparative examples were made into lithium iron phosphate soft-pack batteries with a designed capacity of 5Ah. The positive electrode was LFP:PVDF:SP=96:1.8:2.2, and the current collector was aluminum foil; the negative electrode was graphite:CMC:SBR=97:1.2:1.8, and the current collector was copper foil; the voltage range of the capacity division was 2.0~4.3V. The first efficiency test was charged to 4.3V at 0.1C and discharged to 2.0V at 0.1C; the ratio of the discharge capacity to the charge capacity was calculated. The cyclic charge and discharge performance test was carried out at a current of 1C under a cycle voltage range of 2.0~3.65V, and the capacity retention rate after 500 cycles was calculated and recorded in Table 1.
[0090] Table 1
[0091]
[0092] From the above, it can be seen that in Application Examples 1-4, compared with other coated diaphragms, Application Example 1-2 High Nickel LiNi 0.8 Co 0.1 M 0.1 The O2-coated lithium supplementation agent solution can effectively reduce the internal resistance of the diaphragm, and at the same time achieve a good lithium supplementation effect, improve the initial effect and extend the service life. The lithium supplementation coating diaphragm prepared by the present invention has excellent lithium conductivity, which has a significant improvement effect on the cycle performance of the battery cell.
[0093] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0094] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0095] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A lithium supplementing diaphragm, characterized in that: It includes a separator and a lithium supplement layer provided on the separator, and the lithium supplement layer contains a lithium supplement material; the lithium supplement material has a core-shell structure, the core includes a lithium supplement agent, and the lithium supplement agent is at least one of Li2O, Li2S, and complexes Li2S / Co and Li2O / Co; the shell includes LiNi 1-x-y Co x M y O2, where 0 < x ≤ 0.5, 0 < y ≤ 0.3, x + y < 1, and M includes Mn and / or Al; the thickness of the shell is 50 to 70 nm; the particle size of the lithium supplement material is 300 nm to 1 μm; the lithium supplement layer further contains a binder; the binder is a conductive polymer; the conductive polymer includes at least one of polyacetylene, polypyrrole, polyaniline, polythiophene, and polyfuran; the binder accounts for 0.5% to 20% of the mass of the lithium supplement layer; The lithium supplement material is obtained by the following preparation method, which comprises: A lithium supplement agent precursor is mixed with a shell raw material to form a core-shell coating, wherein the shell raw material includes a soluble Ni salt, a soluble Co salt and a soluble M salt, and the mass ratio of the soluble Ni salt to the lithium supplement agent precursor is controlled to be (1-9):(10-90). The core-shell coating is mixed with a lithium source and sintered, and the amount of the lithium source and the core-shell coating is controlled according to the molar ratio of lithium element to nickel element of (10-100):(3-9) to obtain a lithium supplement material.
2. The lithium supplementing diaphragm according to claim 1, characterized in that: The lithium supplement layer is arranged on a side of the separator facing the positive electrode.
3. A method for preparing the lithium supplementing diaphragm according to claim 1 or 2, characterized in that: The method comprises: A lithium replenishing layer slurry is prepared, wherein, based on the mass of the lithium replenishing layer slurry being 100%, the mass of the lithium replenishing material accounts for 20% to 70%, the mass of the binder accounts for 0.5% to 20%, and the mass of the solvent accounts for 10% to 70%. The obtained lithium replenishing layer slurry is coated on a diaphragm to form a lithium replenishing layer, thereby obtaining a lithium replenishing diaphragm.
4. The method according to claim 3, characterized in that: The preparation method of the lithium supplement material comprises: The lithium supplementing agent precursor is mixed with the shell raw material to form a core-shell coating, and the core-shell coating is mixed with a lithium source and sintered to obtain a lithium supplementing material.
5. The method according to claim 4, characterized in that The lithium supplement material preparation method comprises: firstly mixing a lithium supplement agent precursor with a solvent, then adding a shell raw material and mixing, then adding a mixed solution of ammonia water and a strong base and mixing, and titrating the mixed solution to precipitate a shell precursor, so that the shell precursor simultaneously forms a coating on the lithium supplement agent precursor to obtain the core-shell coating, and then washing and drying the core-shell coating and mixing it with a lithium source and sintering it.
6. The method according to claim 5, characterized in that The shell raw material includes soluble Ni salt, soluble Co salt and soluble M salt; the mass ratio of the soluble Ni salt to the prelithiation agent precursor is (1-9):(10-90); the shell precursor is Ni 1-x-y Co x M y (OH)2, where 0 < x ≤ 0.5, 0 < y ≤ 0.3, x + y < 1, and M includes Mn and / or Al.
7. The method according to any one of claims 4 to 6, characterized in that: The amount of the lithium source and the core-shell coating is controlled according to the molar ratio of lithium element to nickel element of (10-100):(3-9).
Citation Information
Patent Citations
Battery diaphragm and lithium ion battery
CN110197888A
Capacity compensating agent, battery positive electrode and application thereof
CN116130593A
Lithium supplement agent and lithium ion battery using same
CN117558911A
Lithium supplement composite material and preparation method and application thereof
CN117559013A
Cited By
Ceramic composite lithium supplementing diaphragm as well as preparation method and application thereof
CN120657372A
Ceramic composite lithium supplementing diaphragm, preparation method and application thereof
CN120657372B